2019
DOI: 10.1523/eneuro.0070-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Depolarizations Occur in Mild Traumatic Brain Injuries and Are Associated with Postinjury Behavior

Abstract: Millions of people suffer mild traumatic brain injuries (mTBIs) every year, and there is growing evidence that repeated injuries can result in long-term pathology. The acute symptoms of these injuries may or may not include the loss of consciousness but do include disorientation, confusion, and/or the inability to concentrate. Most of these acute symptoms spontaneously resolve within a few hours or days. However, the underlying physiological and cellular mechanisms remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 113 publications
(155 reference statements)
0
16
0
Order By: Relevance
“…The lack of gross motor dysfunction supports that even our RmTBI injury is milder in comparison to other models that typically produce robust motor deficits, as well as gross tissue damage [72][73][74][75] . Our previous study reported no significant motor deficits following a single injury 76 . Even in more mild injuries, motor dysfunction is sometimes detected [77][78][79][80][81][82][83] .…”
Section: Discussionmentioning
confidence: 81%
“…The lack of gross motor dysfunction supports that even our RmTBI injury is milder in comparison to other models that typically produce robust motor deficits, as well as gross tissue damage [72][73][74][75] . Our previous study reported no significant motor deficits following a single injury 76 . Even in more mild injuries, motor dysfunction is sometimes detected [77][78][79][80][81][82][83] .…”
Section: Discussionmentioning
confidence: 81%
“…Two previous studies suggested the occurrence of seizures and SDs in models of mild TBI in mice, based on blood flow measurements [42] and electrophysiological recordings [43]. In the present study, we recorded electrophysiological changes from the cortical surface within seconds following mild and severe TBI in rats.…”
Section: Introductionmentioning
confidence: 70%
“…We first recorded changes in cortical electrocorticography before and immediately after TBI. Following TBI (Figure 1a), the near-direct current recordings showed the characteristic large slow potential change of SD [45], whereas AC recordings showed the rapidly evolving reduction in amplitudes of spontaneous activity that spread along with SD between adjacent recording sites, which is characteristic of spreading depression of activity (Figure 1b-d) [25,34,43,46]. After mild TBI, SDs were observed after 53% of impacts (n = 37 out of 71, Figure 1d), and were recorded within 3 min (124 ± 48 s).…”
Section: Spreading Depolarization Is Common Following Mild and Severe Tbimentioning
confidence: 99%
“…CSD was associated with lower prehospital systolic blood pressure and a poor neurologic recovery (odds ratio [OR] 2.29). 22,23 This electrochemical and neurovascular imbalance explains the frequently observed differences in clinical presentation of lesional CSD symptomatology versus the more benign nonlesional CSD, such as that observed in migraine aura. 24 The incidence of CSD has been reported to be as high as 60% in TBI, 80% in SAH, and over 90% in aggressive strokes.…”
Section: Cortical Spreading Depolarizationmentioning
confidence: 99%